Corporate social responsibility: a likely causality of the crisis or a potential exit strategy component? A proposition development for an economy under pressure. Issue 4 (30th September 2014) - Skouloudis, Antonis; Chymis, Athanasios; Allan, Stuart; Evangelinos, Konstantinos
Abstract : Purpose: – The purpose of this paper is to outline a set of propositions for the Greek business sector concerning the value of strategically adopting a responsible business behaviour. The recent economic downturn of the Greek economy stresses the need for redefining current business models, attitudes and practices. Design/methodology/approach: – The authors draw from prior literature on strategic corporate responsibility and build their arguments on the value of social responsibility as an important component of an exit strategy from the domestic economic crisis. Findings: – Promoting the social responsibility of business could yield win–win opportunities for Greek firms and have a positive effect on the regeneration of the national economy's dynamics. Connecting the well-established strategic CSR literature with the specific handicaps of an economy under pressure, we point out that the current deep crisis can be alleviated by regaining the trustworthiness, supporting the competitiveness potential and enhancing the extroversion of the Greek economy. Practical implications: – Strategic options from which policymakers and managers can endorse the development of a CSR agenda as an exit strategy component are set forth. Such practical implications pertain to the creation of an enabling environment for strategic CSR implementation, an emphasis on CSR-related amelioration of competitiveness parameters and a redefinition of market orientation of domestic firms under the scope of socially responsible business behaviour. Originality/value: – An economic–business environment under extreme pressure is discussed; problems relevant to the Greek case are outlined while a new approach in the way of doing business is proposed.